2019
DOI: 10.1002/pon.5213
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing and responding to chronic cancer‐related fatigue: A meta‐ethnography of qualitative research

Abstract: Objective One of the most prevalent and disrupting symptoms experienced by cancer patients is chronic cancer‐related fatigue (CCRF). A better understanding of the chronic nature of CCRF can provide valuable insights for theory and practice. The purpose of this meta‐ethnography was to derive an overarching interpretative narrative on patients' experiences and responses to CCRF. Methods We conducted a comprehensive systematic literature search in five databases (05‐03‐2018). In addition, papers from reference li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 65 publications
(407 reference statements)
4
37
0
Order By: Relevance
“…Problems related to sleep and fatigue were associated with smaller utility decrements. Although problems with sleep and fatigue are also common among the general population, 55 cancer-related fatigue is especially qualitative and quantitively different, 56,57 which might lead the general population to underestimate its impact. Van Gelder et al 58 recently demonstrated varying QLU-C10D utilities by cancer type and noted that physical functioning, pain and nausea, and vomiting had the largest impact on utilities.…”
Section: Discussionmentioning
confidence: 99%
“…Problems related to sleep and fatigue were associated with smaller utility decrements. Although problems with sleep and fatigue are also common among the general population, 55 cancer-related fatigue is especially qualitative and quantitively different, 56,57 which might lead the general population to underestimate its impact. Van Gelder et al 58 recently demonstrated varying QLU-C10D utilities by cancer type and noted that physical functioning, pain and nausea, and vomiting had the largest impact on utilities.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the MFI-20 with its five dimensions already covers a relatively broad spectrum of fatigue, qualitative studies show further characteristics of this issue. A recent metaanalysis of qualitative studies [37] identified six constructs in the sense of new interpretations of fatigue: embodied experience, (mis)recognition, small horizon, role changes, loss of self, and regaining one's footing. Nevertheless, among the existing fatigue scales, the MFI-20 is one of the best at approaching these additional facets of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…People with significantly depressed mood commonly describe their fatigue as a feeling of heaviness, such that embarking on even simple tasks requires an enormous amount of effort (Matza et al, 2015). People reporting fatigue in the context of cancer commonly mention decreased physical performance, feelings of weakness, and an excessive need to rest after physical activity (Glaus, Crow, & Hammond, 1996), using phrases that often reference the body (e.g., “heavy limbs,” “legs like jelly/wobbly legs,” “feeling weak,” or “the body is worn out”; Bootsma, Schellekens, van Woezik, van der Lee, & Slatman, 2019). These sorts of qualitative analyses provide some useful clues as to how one might further examine the coherence of this construct at different levels of description.…”
Section: Research Implications and Future Recommendationsmentioning
confidence: 99%